2013
DOI: 10.1111/mpp.12075
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression ofGmCaM4in soybean enhances resistance to pathogens and tolerance to salt stress

Abstract: Plant diseases inflict heavy losses on soybean yield, necessitating an understanding of the molecular mechanisms underlying biotic/abiotic stress responses. Ca(2) (+) is an important universal messenger, and protein sensors, prominently calmodulins (CaMs), recognize cellular changes in Ca(2) (+) in response to diverse signals. Because the development of stable transgenic soybeans is laborious and time consuming, we used the Bean pod mottle virus (BPMV)-based vector for rapid and efficient protein expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 56 publications
2
55
0
Order By: Relevance
“…Early transcriptomic analyses indicated that, in Arabidopsis (Arabidopsis thaliana) at least, many CML genes are stress responsive, suggesting a role in Ca 2+ -mediated stress signaling [15]. Subsequent functional analyses by reverse genetics have supported this hypothesis and, to date, several CMLs have been shown to be important during herbivore resistance [16,17], innate immunity [18][19][20][21], salt stress [22], or during both abiotic and biotic stresses, as observed for soybean GmCaM4 [23] and Arabidopsis CML9 [24]. In addition, functional roles in a variety of developmental processes have been uncovered, such as the involvement of Arabidopsis CML23 and 24 in flowering [25], CML42 in trichome branching [26], CML25 in pollen germination and tube elongation [27], CML7 in root hair elongation [28,29], CML39 in seedling establishment [30], and CML20 in microtubule organization [31].…”
Section: Calcium Signaling and Plant Calcium Sensorsmentioning
confidence: 79%
“…Early transcriptomic analyses indicated that, in Arabidopsis (Arabidopsis thaliana) at least, many CML genes are stress responsive, suggesting a role in Ca 2+ -mediated stress signaling [15]. Subsequent functional analyses by reverse genetics have supported this hypothesis and, to date, several CMLs have been shown to be important during herbivore resistance [16,17], innate immunity [18][19][20][21], salt stress [22], or during both abiotic and biotic stresses, as observed for soybean GmCaM4 [23] and Arabidopsis CML9 [24]. In addition, functional roles in a variety of developmental processes have been uncovered, such as the involvement of Arabidopsis CML23 and 24 in flowering [25], CML42 in trichome branching [26], CML25 in pollen germination and tube elongation [27], CML7 in root hair elongation [28,29], CML39 in seedling establishment [30], and CML20 in microtubule organization [31].…”
Section: Calcium Signaling and Plant Calcium Sensorsmentioning
confidence: 79%
“…In addition to biotic stress, CaMs and CMLs are also involved in abiotic stress responses. GmCaM4 , a salt-stress induced gene, has been reported to mediate Ca 2+ signaling and the downstream transcription factor (TF), MYB2 (Rao et al, 2014). In addition, a CaM3 knockout Arabidopsis mutant displayed impaired thermotolerance, whereas overexpression of AtCaM3 increased plant thermotolerance, via interactions with heat stress transcription factors (HSFs) (Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, targeting the 5′ or 3′ untranslated regions that tend to be less conserved can be used to silence individual homologs or a homeologous pair of genes. Rao et al (2014) reported that targeting 198 nucleotides from the 5′ untranslated region of GmCaM4 silenced specifically this gene and resulted in approximately 50 % reduction in transcript levels. To target this sequence, these authors used a BPMV vector that required a single nucleotide change in the cloned sequence in order to change a stop codon into an amino acid-encoding codon.…”
Section: Viruses As Vectors For Vigs In Soybeanmentioning
confidence: 98%
“…BPMV has been used recently to overexpress the soybean calmodulin 4 protein ( GmCaM4) in soybean (Rao et al 2014). Overexpression of GmCaM4 resulted in enhanced resistance to salt stress and infection by the oomycete pathogen Phytophthora sojae and the necrotrophic fungal pathogens Alternaria tenuissima and Phomopsis longicolla.…”
Section: Plant Genesmentioning
confidence: 99%